Simulation of the sensing mechanism in quantum dot gas sensor by quantum light harvesting approach - Suntijitrungruang, Ongart; Lakronwat, Jidapa; Uthailiang, Teerapat; Pongkitiwanichakul, Peera; Boonchui, S. (Frontiers in Chemistry, 2022)
Quantum dot (QD) gas sensors are one of the most useful nanotechnologies applied to protect people from unnecessary harm. This work theoretically explores the mechanism in QD gas sensors in order to advance the prudent design of relevant products. The theoretical model employed in this research is similar to the process in plants’ photosynthesis, referred to as charge separation of light harvesting. In this work, we investigate the details of energy transport in QD gas sensors carried by electrons from the circuit. We demonstrate theoretically how the effects of temperature and gas detection affect electron transport. To analyze thoroughly, the potential energy referred to as the Schotthy barrier perturbed by gasses is considered. Moreover, the energy transfer efficiency (ETE) of QD gas sensors for oxidizing or reducing gas is shown in the simulation. The results imply that the electron transport between QDs (raising the current and lessening the current) depends on a parameter corresponding with the Schotthy barrier. In regard to thermal energy portrayed by phonon baths, a higher temperature shortens the time duration of energy transport in QDs, hence raising energy transfer efficiency and energy current. Our model can be applied to further QD gas sensors’ design and manufacture.